2014
DOI: 10.1111/jfd.12271
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial patterns in tumour prevalence in brown bullhead Ameiurus nebulosus (Lesueur) in the tidal Potomac River watershed (USA)

Abstract: For two decades, fish tumour surveys have been used to monitor habitat quality in the Chesapeake Bay (USA) watershed. Tributaries with sediments contaminated with polynuclear aromatic hydrocarbons (PAHs), known to cause liver neoplasia, were frequently targeted. Here, we compare surveys in brown bullhead Ameiurus nebulosus conducted in 2009-2011 in the tidal Potomac River watershed (including the Anacostia River) with previous surveys. Using logistic regression, we identified length and sex as covariates for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…In the present study, we observed a higher incidence among females than among males. Previous studies have also reported higher tumour prevalence in females than in males (Martineau et al 1990, Keller et al 2011, Pinkney et al 2014, although some studies reported a higher incidence in male than in female fish (Bowser et al 1988, Okihiro 1988, Kortet et al 2003, Korkea-aho et al 2006.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we observed a higher incidence among females than among males. Previous studies have also reported higher tumour prevalence in females than in males (Martineau et al 1990, Keller et al 2011, Pinkney et al 2014, although some studies reported a higher incidence in male than in female fish (Bowser et al 1988, Okihiro 1988, Kortet et al 2003, Korkea-aho et al 2006.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study by Leadley et al (2015) showed Brown Bullheads from contaminated sites in the Detroit River, Michigan-Ontario, had elevated standard metabolic rates related to the environment. Many sites around the Great Lakes, particularly rivers and harbors, still contain high levels of PAHs and other contaminants (Pinkney et al 2004(Pinkney et al , 2014Blazer et al 2009). Despite finding higher standard metabolic rates (SMR) in Brown Bullheads from contaminated sites in the Leadley et al (2015) study, it is unclear how the total metabolic 642 HARTMAN rate (SMR plus active metabolic rate) in contaminated environments compares with that in uncontaminated ones.…”
Section: Model Limitationsmentioning
confidence: 99%
“…; Groff ; Pinkney et al . ). Some virally induced neoplasms in fish occur seasonally (Getchell, Casey & Bowser ).…”
mentioning
confidence: 97%
“…Most are benign epidermal hyperplasias and papillomas, with rare squamous cell carcinomas (Groff ; Roberts ). In the brown bullhead Ameiurus nebulosus (Lesueur), evidence suggests a possible chemical aetiology (Grizzle, Melius & Strength ; Pinkney, Harshbarger & Rutter ), while virus or virus‐like particles have been demonstrated in other species (Coffee, Casey & Bowser ). Some sources relate tumour development to potential interactions between environmental contaminants and viruses (Smith, Ferguson & Hayes ).…”
mentioning
confidence: 99%
See 1 more Smart Citation